2006
DOI: 10.1158/1078-0432.ccr-06-0489
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Angiogenesis by Id-1 through Hypoxia-Inducible Factor-1α–Mediated Vascular Endothelial Growth Factor Up-regulation in Hepatocellular Carcinoma

Abstract: Purpose: Metastasis is commonly associated with poor prognosis of hepatocellular carcinoma (HCC). Being an important angiogenic factor, vascular endothelial growth factor (VEGF) plays a central role in HCC growth and metastasis. Recently, Id-1 (inhibitor of differentiation/DNA synthesis) has been suggested to be a key factor in cancer progression but the molecular mechanism remains unknown. Experimental Design: We first showed that overexpression of Id-1 was correlated with HCC metastasis (P < 0.001) and its e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 38 publications
1
58
0
1
Order By: Relevance
“…Thus, it is possible that ID1 and ID2 have opposite effects on HCC metastasis. Lee et al (32) used a cohort consisting mostly of hepatitis B virus -related HCC. In contrast, our cohort consisted of many HCV-related HCCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is possible that ID1 and ID2 have opposite effects on HCC metastasis. Lee et al (32) used a cohort consisting mostly of hepatitis B virus -related HCC. In contrast, our cohort consisted of many HCV-related HCCs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it is likely that ID1 and ID2 function differently in progression of breast cancer (21,25,29). In the case of HCC, expression of ID1 is increased at early stages of hepatocarcinogenesis (31), and high ID1 expression increases the metastatic potential of HCC (32). It is known that ID2 is expressed at high levels in both human adult and fetal liver tissues (33) but that expression of ID2 decreases in more advanced HCC (34).…”
mentioning
confidence: 99%
“…Id1 activates VEGF by enhancing the stability and activity of HIF-1α (52)(53)(54), and conversely the VEGF/VEGFR2 pathway may activate Id1 (4). Studies in Id1 -/-mice have demonstrated impaired mobilization and recruitment of bone marrow EPCs, leading to impaired tumor angiogenesis and tumor growth (55).…”
Section: Hepatic Mitogensmentioning
confidence: 99%
“…It is also known to bind to phosphorylated Rb. Id1 has recently been associated with transcriptional regulation in the radial growth phase of primary melanomas (29), functions as an angiogenic factor through hypoxia-inducible factor-1a in hepatocellular carcinoma (30), and is implicated into transforming growth factor-h1 suppression of prostate cancer cells (31).…”
Section: Discussionmentioning
confidence: 99%